Autocrine VEGF signalling on M2 macrophages regulates PD‐L1 expression for immunomodulation of T cells. Issue 2 (20th November 2018) - Lai, Yin‐Siew; Wahyuningtyas, Rika; Aui, Shin‐Peir; Chang, Ko‐Tung
Abstract: M2‐polarized macrophages, on one hand, can promote tumour vascularization by producing proangiogenic factors, such as vascular endothelial growth factor (VEGF). On the other hand, the expression of VEGF receptors (VEGFR) in this cell lineage was also reported. Although the function of VEGF/VEGFR axis plays a pivotal role in macrophages infiltration and angiogenesis, however, there is still lack of the direct evidence to show the role of VEGF as an autocrine operating in M2 macrophages, particularly for immunomodulation. In our study, we surprisingly discovered that M2 macrophages polarized by baicalin can simultaneously express VEGF and its receptors. Taking advantage of this unique culture system, we were able to investigate the biological activity of M2 macrophages in response to the autocrine VEGF milieu. Our results showed that the expression of programmed death‐ligand 1 (PD‐L1) on M2 macrophages was significantly up‐regulated in autocrine VEGF milieu. Through the blockade of autocrine VEGF signalling, PD‐L1 expression on M2 macrophages was dramatically down‐regulated. Furthermore, transplantation of PD‐L1 + M2 macrophage stimulated by autocrine VEGF into allogeneic mice significantly suppressed host CD4 + /CD8 + T cells in the peripheral blood and increased CD4 + CD25 + regulatory T cells in the bone marrow. In conclusion, our findings provide a novel biological basis to support the current successful strategy using combined VEGF/PD‐1 signalling blockade in cancer therapy.